Tuberculosis control within Indonesia's hospital accreditation - Puput Oktamianti; Adang Bachtiar; Sutoto Sutoto; Indang Trihandini; Sabarinah Prasetyo; Anhari Achadi; Ferry Efendi (SAGE Publishing, 2021)
Background: Tuberculosis (TB) is an infectious disease that is a major problem in Indonesia, placing Indonesia among the three major countries with the highest TB cases in the world. In addition, reporting of TB data from health service facilities, especially hospitals, is still weak. Since the implementation of Directly Observed Treatment Shortcourse (DOTS) in hospitals in 1995, the number of new TB case reports from hospitals is still low. In order to increase hospital participation in TB control, the government has made a breakthrough strategy, which is the integration of the DOTS strategy in hospital accreditation. Design and methods: This study conducted a literature review and document analysis related TB control standards in hospital accreditation and the implication for the involvement of hospitals in national TB program. This study analyzed regulations, policies, and procedures, including hospital accreditation instruments and annual reports of TB. Results: Accreditation standards related to TB control include: i) Hospital must implement a tuberculosis control program in the hospital, including monitoring and evaluation through activities such as health promotion, tuberculosis surveillance, controlling risk factors, detection and treatment of tuberculosis cases, providing immunity and preventive drugs; ii) Hospital prepares resources for service delivery and tuberculosis control; iii) hospital provides facilities and infrastructures for tuberculosis services in accordance with regulations; and iv) hospital conducts tuberculosis services and efforts to control tuberculosis risk factors in accordance with regulations. Conclusions: Standards and elements of the assessment of TB control components in accreditation are adjusted to the national TB control guidelines.